Terminology Development at Tertiary Institutions: A South African Perspective - Alberts, Mariëtta (Lexikos, 2014)
There is a dire need in South Africa for multilingual polythematic terminology. Currently no tertiary institution presents terminology theory and practice as a fully-fledged subject and there is also no sufficient mechanism for the training of terminologists. This situation provides tertiary institutions the opportunity to position themselves in terms of terminology training and development. Terminology centres at tertiary institutions could be of great value for language as well as all other subject-related departments. The language departments, where such terminology centres could possibly be housed, already have facilities to teach some or all of the official languages of South Africa at tertiary level. Language students could receive postgraduate (and even undergraduate) training in the theory and practice of terminology. For practical work, they could collect terminology at subject-related departments and take it to the terminology centres, where source language terms could be terminographically treated. Subject specialists (i.e. lecturers teaching different subjects) would have to be consulted when defining the concepts and would have to assist language students and their lecturers to supply term equivalents in target languages. This process would enable subject-related and language departments to cooperate in different domains. Language and language departments would therefore become useful to different subject areas. Multilingual polythematic terms with definitions could be available to students who are not proficient in English or Afrikaans. They would therefore have access to study material in their first language. The terminology could be disseminated internally and (inter)nationally through the Internet, which would make it accessible to any other student. This process could best be managed and executed by dedicated terminology centres.